Contact Lens Technology: From Fundamentals to Applications. - Moreddu,R; Vigolo,D; Yetisen,AK (Adv Healthc Mater, 2019)
Contact lenses are ocular prosthetic devices used by over 150 million people worldwide. Primary applications of contact lenses include vision correction, therapeutics, and cosmetics. Contact lens materials have significantly evolved over time to minimize adverse effects associated with contact lens wearing, to maintain a regular corneal metabolism, and to preserve tear film stability. This article encompasses contact lens technology, including materials, chemical and physical properties, manufacturing processes, microbial contamination, and ocular complications. The function and the composition of the tear fluid are discussed to assess its potential as a diagnostic media. The regulatory standards of contact lens devices with regard to biocompatibility and contact lens market are presented. Future prospects in contact lens technology are evaluated, with particular interest given to theranostic applications for in situ continuous monitoring the ocular physiology.